Unilateral renal cystic disease: a case report study - Hakkim, Shameer; R., Babu; K., Kishan Raj; Mallampati, Seetha Rami Reddy (International Journal of Advances in Medicine, 2019)
Unilateral renal cystic disease (URCD) of kidney is a non-familial, extremely rare condition, characterized by replacement of the renal parenchyma of one kidney by a cluster of multiple cysts of varying size with a normal contralateral kidney. It is morphologically indistinguishable from autosomal dominant polycystic kidney disease (ADPKD); as such, hepatic and pancreatic cysts is not seen and shows no progressive deterioration in renal function; thus, differentiating ADPKD from URCD becomes important. We report a case of URCD documented by clinical and radiological imaging. A 21 year-old female, presented with history of mild lancinating pain in the left flank for 6 years which aggravated in the past 3 days, with no history of lower urinary tract symptoms. No significant family illnesses reported. Examination showed normal vitals and ballotability present and associated tenderness on deep palpation in left lumbar region. Laboratory findings were within normal limits. Ultrasonography of abdomen and pelvis showed left hydronephrosis with multiple cysts. CECT Abdomen revealed an enlarged left kidney (∼15×16×10 cm) filled with variable sized round, well-marginated multiple cysts. Renal ultrasound was performed on patient’s parents and her siblings and ruled out cystic renal disease. Hence, authors considered the diagnosis of URCD in this patient. In conclusion, treatment and managing guidelines of URCD have not been mentioned in any of the medical literatures. There is little information regarding the progression of URCD. Hence there is a need for further understanding of pathogenesis, progression and management of these patients.